Bank-SMEs Relationship: A Critical Review of Firm & Industry Specific Determinants Influencing Banks’ Performance - Khalil, Rashid; Shuib, Mohd Sollehudin; Ishak, Suhaimi (Khalsa Publications, 2018)
This study critically reviews the existing literature corresponding to banks’ performance in SMEs sector and investigates the Bank-SMEs relationship. The issues are highlighted with theoretical background of banks’ performance from SMEs financing perspective. Further, it elaborates the financial performance of firms which theoretically supports the banks’ credit rationality. The subsequent sections explain each determinant of SME firms by identifying the theories that individually elucidate firm-specific variables i.e., firms’ performance, financial need, capital structure and growth of banks. Additionally, it explores the association between SMEs loan requirements, length of relationship, product/services and banks’ performance. Moreover, the current study appraises some earlier researches which have examined the direct and indirect relationships among industry specific variables and firm-bank performance. Based on existing information, the final section articulates the gaps identified in literature to summarize the findings and areas for future researches